Study of the ascorbic acid accumulation in Thymus L. genus species of Ukraine flora - O. V. Mazulin; Ya. M. Steshenko; L. A. Fukleva; H. V. Mazulin (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The Thymus L. genus species are extremely widespread in temperate countries and number up to 200 main wild plants, of which up to 50 have been identified in the modern Ukraine flora. Extracts from the official species of the Thymus L. genus are part of effective herbal preparations with pronounced anti-inflammatory, antimicrobial, and antioxidant activities. A promising direction of modern phytochemical research is the determination of the presence and accumulation of biologically active ascorbic acid in the herbs of widespread wild and cultivated species of the Thymus L. genus.